Thigh muscle morphology in football players and skaters - Dong, M.; Zhang, H.; Song, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Skeletal muscle is a very important part of the human locomotive system and muscle plays a fundamental role in exercise. Muscle strength is related to muscular morphology, especially to the cross-sectional area of the muscle. Understanding changes in muscle morphology are important in terms of its relationship with muscular power The present findings will provide information to scientifically develop training programs for athletes whose performance depends upon both strength and power.